PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DALAM PEMBUATAN PASPOR DI KANTOR IMIGRASI KELAS I TEMPAT PEMERIKSAAN IMIGRASI BANDAR LAMPUNG - Adrian Tawai; Rola Pola Anto; Haerul Ikrar Rusli (e-JKPP, 2020)
The lack of good quality of service at the Class I Immigration Office at the Bandar Lampung Immigration Checkpoint can lead to a crisis of trust in the community, which can be in the form of people still feeling convoluted, non-transparent, less informative, less accommodating and inconsistent service procedures and mechanisms so that they do not guarantee legal certainty, time and cost. So that this results in the emergence of other phenomena such as the high costs that must be incurred by the community as users of public services provided by the government. For this reason, bureaucratic reform in the field of public services must be a top priority for the government.The problem in this study can be formulated, namely "does the quality of service affect public satisfaction in making passports at the Class I Immigration Office at the Bandar Lampung Immigration Checkpoint?". This study has the aim of knowing and analyzing the effect of service quality on community satisfaction in making passports at the Class I Immigration Office at the Bandar Lampung Immigration Checkpoint.This study used an explanatory survey design by analyzing the influence of the service quality variable (independent variable) on community satisfaction (dependent variable). The population in this study were the people who made Passports 24 at the Class I Immigration Office at the Bandar Lampung Immigration Checkpoint in 2019, amounting to 1,371 people. The sample in this study was taken 10% x 1.371 = 137.1 ≈ 137 people. The sampling technique used in this study was accidental sampling. The analysis used is descriptive analysis and simple linear regression analysis.Based on the results of data analysis, many respondents who answered about the quality of service complained about the empathy of passport-making employees, especially regarding individual attention, the community was still not satisfied because they did not feel that they had received good service in how employees communicate to the community, were considered less communicative and less effective, this has a significant impact on community satisfaction, especially in terms of getting preferential treatment from employees. There is a positive influence between service quality and community satisfaction in making passports at the Class I Immigration Office at the Bandar Lampung Immigration Checkpoint, which is 27.3%, the rest is influenced by other factors that are not researched, showing that the process of making a passport is not only influenced by service quality. However, there are still many other factors that are not examined such as product quality, emotionality, price and cost.